Xanthohumol Induces Growth Inhibition and Apoptosis in Ca Ski Human Cervical Cancer Cells - Yong, W.K.; Malek, S.N.A. (Hindawi, 2015)
We investigate induction of apoptosis by xanthohumol on Ca Ski cervical cancer cell line. Xanthohumol is a prenylated chalcone naturally found in hop plants, previously reported to be an effective anticancer agent in various cancer cell lines. The present study showed that xanthohumol was effective to inhibit proliferation of Ca Ski cells based on ICvalues using sulforhodamine B (SRB) assay. Furthermore, cellular and nuclear morphological changes were observed in the cells using phase contrast microscopy and Hoechst/PI fluorescent staining. In addition, 48-hour long treatment with xanthohumol triggered externalization of phosphatidylserine, changes in mitochondrial membrane potential, and DNA fragmentation in the cells. Additionally, xanthohumol mediated S phase arrest in cell cycle analysis and increased activities of caspase-3, caspase-8, and caspase-9. On the other hand, Western blot analysis showed that the expression levels of cleaved PARP, p53, and AIF increased, while Bcl-2 and XIAP decreased in a dose-dependent manner. Taken together, these findings indicate that xanthohumol-induced cell death might involve intrinsic and extrinsic apoptotic pathways, as well as downregulation of XIAP, upregulation of p53 proteins, and S phase cell cycle arrest in Ca Ski cervical cancer cells. This work suggests that xanthohumol is a potent chemotherapeutic candidate for cervical cancer.